2007
DOI: 10.1111/j.1442-9993.2007.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of low intensity fire on soil macroinvertebrate assemblages in different vegetation patch types in an Australian tropical savanna

Abstract: Early dry season fires are a common land management regime employed across the tropical savannas of northern Australia. The rationale is that this reduces fuel loads and so reduces fire risk in the latter part of the dry season. Despite the acceptance of fire as a major management tool the ecological effects of fire remain uncertain. Vegetation patches and their associated macroinvertebrates play a critical role in the capture and recycling of water and nutrients. The aim of this study was to examine the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…He found termite richness to be slightly higher in the seasonally burned forest but relative abundance data were not collected. In an Australian tropical savanna, Dawes-Gromadzki [45] found termite abundance declined in tree patches following an early dry-season burn. Most recently, Davies et al [16] found termites to be highly resistant to fire in African savannas although tolerance varied considerably among functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…He found termite richness to be slightly higher in the seasonally burned forest but relative abundance data were not collected. In an Australian tropical savanna, Dawes-Gromadzki [45] found termite abundance declined in tree patches following an early dry-season burn. Most recently, Davies et al [16] found termites to be highly resistant to fire in African savannas although tolerance varied considerably among functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…(1976), Benzie (1986), Ferrar (1982), Desouza et al . (2003), Dawes‐Gromadzki (2007) and Traoré and Lepage (2008). These constitute four from Africa, and one each from South America and Australia.…”
Section: Current Knowledge Statusmentioning
confidence: 99%
“…1976; Benzie 1986; Traoré & Lepage 2008) and three with single‐fire events (Ferrar 1982; Desouza et al . 2003; Dawes‐Gromadzki 2007). The three studies dealing with fire regimes (all conducted in Africa) considered only two extreme regimes: that of fire exclusion and of annual burns.…”
Section: Current Knowledge Statusmentioning
confidence: 99%
“…Through their mound-building activities, termites enrich soils, contribute to both large-and small-scale habitat heterogeneity, and provide critical resources to a diverse suite of species on many continents (e.g., West Africa, Konate et al 1999, Ndiaye 2004Australia, Black and Okwakol 1997;Europe, Wolters 2000;andNorth America, Nash andWhitford 1995, Fox 2003). How these potential ''islands of fertility'' (Schlesinger et al 1996, Lavelle et al 1997, Dawes-Gromadzki 2007 created by termite mounds affect measures of plant fitness is largely unknown. In addition, the effects of soil enrichment by termites might be enhanced or diminished by vertebrate herbivores that preferentially graze on mound grasses and deposit nutrients in dung and urine.…”
Section: Introductionmentioning
confidence: 99%